Pengaruh Media Vidio Pembelajaran terhadap Hasil Pembelajaran Tematik pada Siswa Kelas VI SD Negeri Kejawat Kecamatan Brang Rea Kabupaten Sumbawa Barat - Faridah (Yayasan Pembina Lembaga Pendidikan (YPLP) PGRI Kabupaten Sumbawa Barat - NTB - Indonesia, 2020)
This study aims to determine the effect of the use of video learning media on thematic learning outcomes in SD Negeri Kejawat, Brang Rea District, West Sumbawa Regency, 2019/2020 academic year. This research was conducted in 2 cycles with 1 meeting per cycle. The research subjects were teachers and students of grade VI SD Negeri Kejawat, Brang Rea District, West Sumbawa Regency, in the 2019/2020 academic year with a total of 5 students. Data were collected using test and non-test techniques. Data analysis used quantitative and qualitative descriptive analysis. The results showed that using instructional video media could improve the thematic learning outcomes of Theme 2 (Unity in Differences) in Class VI SD Negeri Kejawat, Brang Rea District, West Sumbawa Regency, namely: (1) The skills of teachers through the use of video learning media increased. The increase in teacher skills was 18.73% from 72.93% in the first cycle with a good category to 91.66% in the second cycle with a very good category. (2) Student activity through the use of learning video media increased. The increase in student activity was 13.47% from 68.33% in the good category in the first cycle to 81.80% in the second cycle with a very good category. (3) Student learning outcomes through the application of learning video media have increased. Student completeness increased by 60% from 40% at the end of the cycle I to 100% at the end of cycle II. The data has reached the established success indicator of 80%.